PENDIDIKAN DEMOKRASI PESANTREN PEMIKIRAN REFLEKTIF TRADISI PESANTREN DI NTB - Taufik, Muhammad (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
Education on democracy is something new to pesantren. This is because, in the pesantren curriculum, democracy education is not explicitly prescribed. Implicitly, however, pesantren community has played some roles in the democratization process, both within the pesantren and at the national level. Generally speaking, pesantren in NTB have opened the door for the changes in the educational system that take place outside the pesantren, including the discourse on democracy education. The involvement of Tuan Guru in the legislative body has clearly given indication of their roles and contribution in the process of democratization.